Blockchain-based taffic condition early-warning scheme for VANET - Chunyan LI; Jia ZHAO; Jiqiang LIU; Qiang ZHANG; Lei HAN (网络与信息安全学报)
Road conditions early-warning scheme is effective solution to solve vehicle congestion and traffic accidents of VANET.The current traffic conditions in China as well as the development and application of VANET were analyzed.Combined with blockchain technology,a blockchain-based traffic conditions early-warning scheme for VANET was proposed.The Hyperledger Fabric alliance chain technology platform is used to simulate this scheme.The experimental results show that the scheme is reasonable and feasible.